Pengukuran Kualitas Produk EQ Spacing Dengan Metode Statistic Quality Control (SQC) Dan Fault Tree Analysis (FTA) Di PT Sinar Semesta - Rudi Setiadi; Ari Zaqi Al Faritsy (Politeknik Kampar, 2024)
PT Sinar Semesta is an industrial company engaged in metal casting. The problems that arise at PT Sinar Semesta are what type of disability is the most dominant and what factors influence the type of disability. The purpose of this research is to find out the types of product defects, and the solutions that can be taken to overcome these problems. This study uses the Statistical Quality Control (SQC) method used to control quality from the initial process to the finished product and Fault Tree Analysis (FTA) is used to determine what factors cause defects in the product. Based on the results of a pareto chart analysis from November 2021 to October 2022, the total production was 3008 products, there were 838 defective products. There are two types of defects in the Eq Spacing product, including defects in the tail of rats obtained at a percentage of 91.53% with a cumulative percentage of 91.53% and water defects obtained at a percentage of 8.47% with a cumulative percentage of 100%. Factors causing defects with the greatest weight are careless operators and fatigue for the proposal obtained, namely supervising workers so that accuracy can be maintained.